2009
DOI: 10.1099/vir.0.014449-0
|View full text |Cite
|
Sign up to set email alerts
|

Multiple novel astrovirus species in human stool

Abstract: Diarrhoea remains a significant cause of morbidity and mortality in developing countries where numerous cases remain without identified aetiology. Astroviruses are a recently identified cause of animal gastroenteritis which currently includes two species suspected of causing human diarrhoea. Using pan-astrovirus RT-PCR, we analysed human stool samples from different continents for astrovirus-related RNA sequences. We identified variants of the two known human astrovirus species plus, based on genetic distance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

7
227
1
12

Year Published

2013
2013
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 223 publications
(247 citation statements)
references
References 32 publications
7
227
1
12
Order By: Relevance
“…Similarly, clinical studies investigating infantile diarrheal samples in India, the United States, Egypt, and China reported the more frequent occurrence of MLB-AstVs than VA-AstVs (22,49,50). A previous clinical study reported the less frequent detection of MLB-AstV, but the study investigated samples from adults with diarrhea and children without diarrhea (20). These observations suggest that MLB-AstVs may be more prevalent than VA-AstVs among children with diarrheal disease.…”
Section: Discussioncontrasting
confidence: 44%
See 4 more Smart Citations
“…Similarly, clinical studies investigating infantile diarrheal samples in India, the United States, Egypt, and China reported the more frequent occurrence of MLB-AstVs than VA-AstVs (22,49,50). A previous clinical study reported the less frequent detection of MLB-AstV, but the study investigated samples from adults with diarrhea and children without diarrhea (20). These observations suggest that MLB-AstVs may be more prevalent than VA-AstVs among children with diarrheal disease.…”
Section: Discussioncontrasting
confidence: 44%
“…The presence of these novel AstVs has been documented in several countries, including Australia, China, India, Nepal, the Netherlands, Nigeria, Pakistan, and the United States, but not in Japan (19,20,22,23,47,48). We identified MLB-AstVs in all influent samples collected between November 2007 and March 2008.…”
Section: Discussionmentioning
confidence: 86%
See 3 more Smart Citations